Pharmacological Signatures of the Exenatide Nanoparticles Complex Against Myocardial Ischemia Reperfusion Injury - Yi Zhang; Ping Qian; Hong Zhou; Ruilin Shen; Bo Hu; Yajun Shen; Xiaofang Zhang; Xiaohua Shen; Guangtao Xu; Limin Jin (Karger Publishers, 2018)
Background/Aims: Myocardial ischemia/reperfusion (I/R) injury (MI/RI) is a critical cause of death in patients with heart disease. However, the pharmaco-therapeutical outcome for MI/RI remains unsatisfactory. Innovative approaches for enhancing drug sensitivity and recovering myocardial function in MI/RI treatment are urgently needed. The purpose of this study was to evaluate the protective effects of exenatide-loaded poly(L-lysine)-poly(ethylene glycol)-poly(L-lysine) (PLL-PEG-PLL) nanoparticles (NPs) against MI/RI. Methods: The size of PLL-PEG-PLL NPs and the loading and release rates of exenatide were determined. The in vitro NP cytotoxicity was evaluated using newborn rat cardiomyocytes. Rats pretreated with free exenatide or exenatide/PLL-PEG-PLL polyplexes were subjected to 0.5-h ischemia and 2-h reperfusion in the left anterior descending coronary artery. The histopathologic lesions were assessed using hematoxylin-eosin staining. The general physiological indices, including blood pressure (BP), heart rate (HR), the left ventricular ejection fraction (LVEF) and end-diastolic pressure (LEVDP), and the left ventricular pressure maximal rate of rising (dp/dtmax), were monitored using a non-invasive blood pressure analyzer and color Doppler echocardiography. The antioxidative activity in the myocardial tissue was measured. The myocardial enzymatic activity was further estimated by determining the serum levels of creatine kinase (CK), lactate dehydrogenase (LDH), cardiac troponin T (cTnT), and glucagon-like peptide-1 (GLP-1), as well as the expression of GLP-1R in the myocardial tissue. Results: Exenatide preconditioning attenuated the oxidative stress injury and promoted the myocardial function in I/R-induced myocardial injury, while the application of block copolymer PLL-PEG-PLL as a potential exenatide nanocarrier with sustained release significantly enhanced the bioavailability of exenatide. Conclusion: The block copolymer PLL-PEG-PLL may function as a potent exenatide nanocarrier for augmenting pharmacotherapy against MI/RI with unprecedented clinical benefits. Further study is needed to better clarify the underlying mechanisms.